MicroRNA profile and adaptive response to exercise training: A review - Domanska-Senderowska, D.; Laguette, M.-J. N.; Jegier, A.; Cieszczyk, P.; September, A. V.; Brzezianska-Lasota, E. (International Journal of Sports Medicine, 2019)
MicroRNAs are small non-coding regulatory RNAs which may be released into the systemic circulation as a consequence of the body's adaptation to exercise. The expression profile of circulating miRNAs (ci-miRNAs) has been proposed as a potential diagnostic biomarker for adaptive responses of particular systems to physical exertion. Several miRNAs are recognized as regulators of signalling pathways such as the IGF1/PI3K/AKT/mTOR axis, relevant to exercise adaptation. MicroRNA levels may fluctuate depending on training type/exercise regimen in correlation with phenotypic features such as VO2 max. Muscle-specific miRNAs have been proposed as regulators of skeletal muscle/myocardial interactions during physical exertion, thereby facilitating adaptation. Differential expression of miRNAs may relate to molecular patterns of communication triggered during/after exercise as response, recovery and adaptation mechanisms to training load. This review highlights recent findings and the potential significance of specific miRNAs in the process of exercise adaptation. Altered ci-miRNA profiles following exercise suggest that they may be useful biomarkers of health and adaptation to intervention strategies. Identification of the concert of miRNA expression signatures together with their targets is critical towards understanding gene regulation in this context. Understanding how the external environment influences gene expression via miRNAs will provide insight into potential therapeutic target strategies for disease.